Plaster body wrap: effects on abdominal fat - Moreira, Juliana Santos (2013)
Abdominal fat is associated with metabolic disorders, leading to cardiovascular risk factors and numerous diseases. This study aimed to analyze the effect of plaster body wrap in combination with aerobic exercise on abdominal fat. Methods: Nineteen female volunteers were randomly divided into intervention group (IG; n = 10) performing aerobic exercise with plaster body wrap, and control group (CG; n = 9) performing only exercise. Subcutaneous and visceral fat were measured using ultrasound; subcutaneous fat was also estimated on analysis of skinfolds and abdominal perimeters. At the end of the 10-sessions protocol, the IG demonstrated a significant decrease (p ≤ 0.05) in subcutaneous fat at the left anterior superior iliac spine (ASIS) level and in iliac crest perimeter measurements. A large intervention effect size strength (0.80) was found in subcutaneous fat below the navel and a moderate effect size strength on the vertical abdominal skinfold (0.62) and the perimeter of the most prominent abdominal point (0.57). Comparing the initial and final data of each group, the IG showed a significant decrease in numerous variables including visceral and subcutaneous fat above and below the navel measured by ultrasound (p ≤ 0.05). Plaster body wrap in combination with aerobic exercise seems to be effective for abdominal fat reduction.